2005
DOI: 10.1017/s1752756200010206
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to estimate the intake of grass by ponies with restricted access to pasture

Abstract: It has been shown that horses and ponies at pasture usually graze for 15-17 hours per day, and consume between 16 and 33g dry matter (DM) /kg live weight per day, depending on animal size and physiological status. However, many predominantly stabled horses have restricted access to pasture, often only 1-3 hours/day. There is no information on voluntary food intake (VFI) of horses under such regimens. Therefore the aim of this pilot study was to determine the voluntary intake of fresh herbage by ponies when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, this potential survival strategy could be a problem when managing obese domestic horses and ponies (easy-keepers), when kept on restricted access to pasture (shorter grazing turnout periods or limited sward height) designed to reduce their caloric intake (Geor 2010). Horses and ponies are capable of increasing their forage consumption during restricted grazing periods by increasing the rate of feed intake, with reports of ~40% of daily DMI consumed by ponies during a 3-h restricted grazing turnout (Ince et al 2005), and greater mean rates of DMI observed in horses during 3-and 6h restricted grazing turnouts than during 24-h access to grazing (Glunk et al 2013a). Although restricting pasture access decreases the total intake of pasture, the compensatory increase in the rate of feed intake (during the turnout period) and the longer MRT of digesta (due to the restricted feeding time) may enable horses and ponies to maintain BW even when the quantity of feed is restricted (Dugdale et al 2011;Argo et al 2012;Glunk et al 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…However, this potential survival strategy could be a problem when managing obese domestic horses and ponies (easy-keepers), when kept on restricted access to pasture (shorter grazing turnout periods or limited sward height) designed to reduce their caloric intake (Geor 2010). Horses and ponies are capable of increasing their forage consumption during restricted grazing periods by increasing the rate of feed intake, with reports of ~40% of daily DMI consumed by ponies during a 3-h restricted grazing turnout (Ince et al 2005), and greater mean rates of DMI observed in horses during 3-and 6h restricted grazing turnouts than during 24-h access to grazing (Glunk et al 2013a). Although restricting pasture access decreases the total intake of pasture, the compensatory increase in the rate of feed intake (during the turnout period) and the longer MRT of digesta (due to the restricted feeding time) may enable horses and ponies to maintain BW even when the quantity of feed is restricted (Dugdale et al 2011;Argo et al 2012;Glunk et al 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fructan content of Meadow Fescue may be undetectable at 11-25°C and as high as 220 g/kg DM grass at 5-10°C (Longland & Cairns 2000). Hoffman et al (2001) showed the largest changes in grass carbohydrate content to occur in the spring and autumn (Ince et al 2005) and that horses can consume up to 1.3% bodyweight as DM in an 8-hour grazing period (Dowler 2009). Hoffman et al (2001) showed the largest changes in grass carbohydrate content to occur in the spring and autumn (Ince et al 2005) and that horses can consume up to 1.3% bodyweight as DM in an 8-hour grazing period (Dowler 2009).…”
Section: Pathophysiology Of Nutritional Colic and Diarrheamentioning
confidence: 99%
“…Ponies have been observed to consume 40% of their daily DM intake during 3 hours of pasture turnout (Ince et al 2005) and can ingest up to 1% of BW as DM within 3 h of pasture turnout (Longland et al 2011a). Ponies have been observed to consume 40% of their daily DM intake during 3 hours of pasture turnout (Ince et al 2005) and can ingest up to 1% of BW as DM within 3 h of pasture turnout (Longland et al 2011a).…”
Section: Feed Non-structural Carbohydrate Contentmentioning
confidence: 99%